Studi Empiris Tentang Kompetensi Auditor Dalam Melakukan Fungsi Audit Internal Pada Bank Pembiayaan Rakyat Syariah - Pradesa, Hafid Aditya; Agustina, Iin; Sulistyan, Riza Bahtiar; Rusdianti, Imanita Septian (Magister Akuntansi Universitas Pancasila, 2023)
Auditor competence is important in supporting the quality of the implementation of internal audits, including the Islamic People's Financing Bank (BPRS). This study aims to explore aspects of auditor competence, especially in performing the internal audit function at BPRS. Specifically, this study seeks to reveal which aspects or performance criteria are most important and which need a lot of improvement in the function area of carrying out the internal audit function in BPRS. Research instruments that adopt national work competency standards (SKKNI number 38 year 2017) are distributed online to auditors from BPRS within the Province of East Java. A total of 41 auditors were respondents in this study. By using a quantitative method, this research is more descriptive, especially in testing the constructs about carrying out the audit function in the BPRS with the national work competency standards that apply in Indonesia. The results reveal that the instruments used are valid and reliable. Descriptively, the implementation of the audit function at the BPRS is in a good category, but there is still some potential for room for improvement and improvement in the quality of auditing at the BPRS in the future.